Kajian Peranan Desain UX (Pengalaman Pengguna) - UI (Antar Muka Pengguna) Mobile Application Kategori Transportasi Online terhadap Gaya Hidup Bertransportasi Masyarakat Urban - Edo Tirtadarma; Agung Eko Budi Waspada; Elda Franzia Jasjfi (Universitas Trisakti, 2018)
The role of digital and internet technology, and the presence of smartphones have created two-way communication between users and digital application manufacturers. Users are connected by applications that are downloaded into their smartphone so they can commuicated, sharing information. As the resuluts of the existence of mobile application in modern era nowadays, that the user will feel easier while doing their daily activities. Users can also choose the type or category of mobile application that suits their needs.The category of online transportation, is a mobile application that is often used by users in modern era in the last five years. The beginning of online transportation was started by Uber, the first online mobile application based transportation that was present in Jakarta, and then it was followed by Go-Jek and Grab. The three online transpotrations come as a solution to transportation problem in urban city, Jakarta. In this thesis the researcher will analyzing the role of user experience (UX) and user interface (UI) mobile application online transportation category from visual communication perspective, so the mobile application that are made can give a solution in transportation needs and friendly user. Also in this research, the reseracher also analyze the effect of UX-UI on the lifestyle transportation in urban city, Jakarta. It is expected that in the future this research can assist designers in designing mobile application with UX-UI that are gave useful outcome for user's life, viewed from the design perspective. The methodology that is used in this thesis research is qualitative methodology, with case study analysis technique. The result of this research is the difference of user experience between the three online transportation company was made due to different vision and mission of each company, which effected the difference of their user interface. UX-UI that has difference between Grab, Go-Jek and Uber gave result in difference mindsets that casue difference motivation of each user while they using Grab, Go-Jek and Uber and thereby causing different lifestyle when using mobile application online transportation AbstrakPeranan teknologi digital dan internet, serta keberadaan telepon genggam pintar (smartphone) telah menciptakan komunikasi dua arah, antara pengguna (user) dan produsen. Para user dihubungkan oleh aplikasi yang terunduh pada mobile application. Dampak dari keberadaan mobile application, adalah pengguna (user) akan merasa dimudahkan dalam menjalankan aktivitas sehari-harinya. Pengguna juga bisa memilih tipe atau kategori mobile application yang sesuai dengan kebutuhan mereka Kategori transportasi online, merupakan mobile application yang sering digunakan oleh para pengguna (user) dalam rentang waktu lima tahun terakhir. Diawali oleh kemunculan Uber, mobile application transportasi berbasis online pertama yang hadir di Jakarta, disusul oleh Go-Jek dan Grab. Ketiga produsen transpotrasi online ini hadir sebagai solusi permasalahan transportasi di kota urban, Jakarta. Pada tesis ini akan diteliti peranan dari user experience (UX) dan user interface (UI) pada mobile application transportasi online dilihat dari kacamata desain komunikasi visual, sehingga mobile application yang dibuat bisa memenuhi kebutuhan akan transportasi dan mudah digunakan oleh pengguna (user). Serta pengaruh UX-UI terhadap gaya bertransportasi masyarakat urban. Diharapkan di masa depan penelitian ini dapat membantu para desainer dalam mendesain mobile application dengan kaidah UX-UI yang berguna bagi kehidupan user, dilihat dari kacamata desain. Metodologi yang dipakai dalam penelitian tesis ini adalah metodologi penelitian kualitatif, dengan teknik analisis studi antar kasus. Hasil dari penelitian ini adalah ditemukannya perbedaan user experience antara ketiga penyedia jasa transportasi online, dikarenakan perbedaan visi misi perusahaan yang berbeda, yang mengakibatkan perbedaan user interface. Perbedaan UX-UI antara Grab, Go-Jek dan Uber pada akhirnya mengakibatkan perbedaan pola pikir yang melandasi motivasi masing-masing user dalam menggukaan Grab, Go-Jek dan Uber sehingga menyebabkan perbedaan gaya bertransportasi (lifestyle) yang berbeda pula saat menggunakan mobile application transportasi online.